Monitoring of the internal temperature of hives of Africanized bees Apis mellifera L. in Cocal - PI (Research, Society and Development, 2022)
The monitoring the internal thermoregulation of the hives and the environment of the apiary become essential for the success of the production system, since they can affect the development of the offspring and daily activities carried out by the bees, and in this sense, the objective was to monitor the temperature. in hives of Africanized bees Apis mellifera L. in the municipality of Cocal-PI from January to October 2021. The results collected during the productive cycle (rainy and dry period) indicated that the internal temperature in the hives of Africanized bees fluctuated throughout the months, from January to October, in compliance with the recommendations. Environmental temperatures declined as the months of the year passed, with the highest temperatures being observed in January, with an average of 34.1ºC and rising during the dry period of the year, reaching an average value of 33.8ºC in October. The africanized Apis mellifera bees maintain nest homeostasis in the dry and rainy period of the year. The air humidity behaved contrary to the temperature of the environment in the rainy season, increasing with the passing of the months, while, in the dry period of the year, there was a reduction in air humidity. Africanized Apis mellifera bees maintain nest homeostasis in the dry and rainy period of the year. There are internal temperature variations in hives throughout the year without altering the internal homeostatic balance. Fluctuations in air humidity and ambient temperatures are due to variations in climatic conditions throughout the months of the year.